Hygrothermal simulations of thermally insulated basement envelopes - Importance of boundary conditions below grade. (15th July 2021) - Asphaug, Silje Kathrin; Time, Berit; Kvande, Tore
Abstract: Hygrothermal simulations are widely used to predict and optimise the hygrothermal performances of building envelopes. For the walls and floors in basements, however, determining the variation of the exterior hygrothermal boundary conditions below grade are challenging due to the various and complex heat and moisture loads and the large area needed to simulate the surrounding ground. A scoping literature review is conducted to provide an overview of current state-of-the-art methods for the addressing of these boundaries. Ten of the most comprehensive studies are selected and scrutinised. The review shows that there is a lack of thorough validation for hygrothermal simulations of basements using full-scale physical measurements. The most valuable experiences from studies with somewhat different perspectives are identified. Key uncertainties include the soil's varying composition and moisture content, liquid uptake at the soil surface and transfer of precipitation, and computational costs. Finally, the review highlights the need for a recognised method/procedure to determine the exterior boundary conditions for hygrothermal simulations of basement envelopes, which can account for the varying influencing factors of the ground. Not only can a better understanding and prediction of heat and moisture performance of basement envelopes contribute to improving building durability and energy efficiency; it can also potentially result in significant economic savings, as expensive repairs below grade can be avoided or delayed. Highlights: Reviews state-of-the-art hygrothermal simulations methods for basement envelopes. Shows the lack of validation with physical measurements below grade. Identifies valuable experiences related to numerical simulations of the ground. Shows the need for predefined boundary conditions below grade in hygrothermal tools.